A systematic review and meta‐analysis of delayed help‐seeking, delayed diagnosis and duration of untreated illness in bipolar disorders. (22nd September 2022) - Scott, Jan; Graham, Anna; Yung, Alison; Morgan, Catherine; Bellivier, Frank; Etain, Bruno
Abstract: Objectives: To examine the time delay between the age at onset of symptoms or episodes of bipolar disorders (BD) and the age at diagnosis of and/or receipt of clinical practice guideline recommended interventions for BD. Methods: Systematic search of five databases to identify publications from January 2000 to July 2022 that reported one or more of the following reliable and valid estimates of latency: delay in help seeking (DHS), delay in diagnosis (DD) and duration of untreated BD (DUB). Eligible studies were included in random effects meta‐analyses and multivariate meta‐regression was used to assess factors associated with each latency construct. Results: Screening of 1074 publications identified 59 eligible studies (reported in 66 publications) of >40, 000 individuals that estimated DHS (8 studies), DD (20 studies) and/or DUB (45 studies). The median DHS, DD and DUB were 3.5 (IQR: 2.8, 8.48), 6.7 (IQR: 5.6, 8.9) and 5.9 years (IQR: 1.1, 8.2), respectively. Key factors associated with shorter DD included older age and residing outside North America; shorter DUB was associated with psychotic or manic onset and access to early intervention services. Conclusions: Greater consensus on definitions of latency constructs and better‐quality targeted research is required regarding DHS, DD and DUB. This review suggests that, while the peak age at onset of BD is 15–25, diagnosis and guideline recommended interventions (e.g., mood stabilizers) are likely to be delayed until age 25–35 years except for a minority of individuals with access to early intervention services.